Analysis Rice Field Drought Potential using the Standardized Precipitation Index (SPI) Method - Rival Doli Yusman; Fadli Irsyad; Feri Arlius; Rizky Armei Saputra; Delvi Yanti (The University of Lampung, 2025)
Drought analysis can be used as an early warning of drought in rice fields, which can be identified by connecting various parameters. This study aims to identify the potential for rice fields vulnerable to drought in Agam Regency. Drought is primarily caused by uneven rainfall distribution, leading to imbalanced hydrological conditions. This study used the last 30 years of rainfall data (1993 2022) from five stations located at Agam Regency (Canduang and Gumarang) and the rest outside of the study area (Padang Panjang, Suliki, and Paraman Talang). Spatial analysis of drought distribution was carried out using the Inverse Distance Weighted (IDW) method. The results showed the consistency test value of rainfall data for all five stations was obtained with an average of R² with a value of 0.992, the potential area of rice fields with a dry and very dry category was 13,640.61 ha and 904.55 ha, respectively. The conclusions of this study are (i) the districts with the most potential to be affected by drought (dry and very dry categories) are Tilatang Kamang and Malalak District, with an area of 2,058.15 ha and 750.48 ha, respectively, (ii) it is important to prepare the water shortage in the dry season by utilizing rivers, irrigation and reservoirs in the area. Keywords: Agam Regency, Drought Potential, Rain, Rice Fields, SPI.